METODE PERHITUNGAN VARIABEL COSTING DALAM MENGINDENTIFIKASI HARGA POKOK PRODUKSI PADA UMKM WARTEG QUEEN - Fadillah, Rifky; Nuthajijah, Ristia; Azzahra, Revaneyna; Azzahra, Naswa Natania; Putra, Seldy Chandra; Muawiyah, Salma Safitri; Akbar, Silvia; Situngkir, Tiar Lina (Journal for Management Student (JFMS), 2024)
This research focuses on the use of the variable costing method in calculating production costs for determining selling prices. Research objectives: 1. Determination of the cost of goods according to Warteg Queen. 2. To determine the cost of goods using the variable costing method at Warteg Queen. 3. To determine the effect of changes in the method of calculating the cost of products on profits at Warteg Queen.